Implementation Of Promotional Mix Strategies For School Admission At Madrasah Aliyah Negeri - Jamilatul Ilmiyah; Siti Aminah (JIEMAN: Journal of Islamic Educational Management, 2023)
An educational institution is an organization that produces services which are then purchased by consumers, namely the public. Therefore, marketing or promotional activities are very necessary in schools, especially in admissions activities for new students. The importance of promoting a school requires a special strategy so that promotion can run smoothly, because with appropriate and effective promotion, a school can attract prospective students and the school can get students according to the school's expectations. The focus of the research examined includes: 1) How is the promotional mix strategy planned for accepting new students at Madrasah Aliyah Negeri 1 Jember?; 2) How is the promotion mix strategy implemented in accepting new students at Madrasah Aliyah Negeri 1 Jember?; 3) How is the promotion mix strategy evaluated in accepting new students at Madrasah Aliyah Negeri 1 Jember? The aim of this research is to describe the planning, implementation and evaluation of promotional mix strategies in admitting new students at Madrasah Aliyah Negeri 1 Jember. This research uses descriptive qualitative research methods. The data collection techniques use observation, interviews and documentation. Meanwhile, data analysis uses the Miles, Huberman and Saldana model which includes data collection, data condensation, data presentation and drawing conclusions. Data validity uses source triangulation and technical triangulation. The results of this research are: 1) Planning a promotional mix strategy for accepting new students including: needs analysis, program preparation, and school coordination meetings. 2) Implementation of the promotional mix strategy for accepting new students including: advertising, personal selling, publicity, sales promotion. 3) evaluation of promotional mix strategies for new student admissions including: advertising evaluation, personal selling evaluation, publicity/public relations evaluation, and sales promotion evaluation Lembaga pendidikan merupakan suatu organisasi yang menghasilkan jasa yang kemudian jasa dari lembaga pendidikan dibeli oleh konsumen yaitu masyarakat. Oleh karena itu kegiatan pemasaran atau promosi sangat diperlukan dalam sekolah terutama dalam kegiatan penerimaan siswa baru. Pentingnya mempromosikan sekolah sehingga membutuhkan strategi khusus agar promosi dapat berjalan lancar, karena dengan promosi yang tepat dan efektif maka sebuah sekolah dapat menarik calon siswa dan sekolah bisa mendapatkan siswa sesuai dengan harapan sekolah.  Fokus penelitian yang diteliti diantaranya: 1) Bagaimana perencanaan strategi bauran promosi dalam penerimaan peserta didik baru di Madrasah Aliyah Negeri 1 Jember?; 2) Bagaimana pelaksanaan strategi bauran promosi dalam penerimaan peserta didik baru di Madrasah Aliyah Negeri 1 Jember?; 3) Bagaimana evaluasi strategi bauran promosi dalam penerimaan peserta didik baru di Madrasah Aliyah Negeri 1 Jember?. Tujuan dari penelitian ini adalah untuk mendeskripsikan perencanaan, pelaksanaan, dan evaluasi strategi bauran promosi dalam penerimaan peserta didik baru di Madrasah Aliyah Negeri 1 Jember. Penelitian ini menggunakan metode penelitian kualitatif deskriptif. Adapun teknik pengumpulan data menggunakan observasi, wawancara, dan dokumentasi. Sedangkan analisis data menggunakan model Miles, Huberman dan Saldana yang meliputi pengumpulan data, kondensasi data, penyajian data dan penarikan kesimpulan. Keabsahan data menggunakan triangulasi sumber dan triangulasi teknik. Adapun hasil dari penelitian ini adalah: 1) Perencanaan strategi bauran promosi penerimaan peserta didik baru meliputi: analisis kebutuhan, penyusunan program, dan rapat koordinasi sekolah. 2) Pelaksanaan strategi bauran promosi penerimaan peserta didik baru meliputi: periklanan, personal selling, publisitas, salespromotion. 3) evaluasi strategi bauran promosi penerimaan peserta didik baru meliputi: evaluasi periklanan, evaluasi personal selling, evaluasi publisitas/hubungan masyarakat,  dan evaluasi salespromotion.